Treatment and water reuse of lead-zinc sulphide ore mill wastewaters by high rate dissolved air flotation. (October 2018) - Azevedo, A.; Oliveira, H.A.; Rubio, J.
Graphical abstract: Highlights: The work dealt with solids, Pb 2+ and Cu 2 ion removal from mining wastewater by DAF. Removal values were >95% after adsorption onto flocs of ferric hydroxide carrier. The treated water was free from ions which might activate ZnS in rougher flotation. The DAF design was innovative, tall cell and with lamellae and a perforated plate. The hydraulic loading was 15 m h −1, more than twice that of conventional DAF cells. Abstract: Simulated wastewaters (concentrate and tailings thickener overflows), from a future lead-zinc flotation separation plant, were treated for the removal of target metal ions (Zn 2+, Pb 2+ and Cu 2+ ) and suspended solids (0.1–0.5 g L −1 ). The ions were adsorbed onto ferric hydroxide precipitates, and then removed by dissolved air flotation (DAF). Best results obtained at bench scale were validated at pilot scale, employing i. 15–20 mg L −1 Fe 3+ (chloride salt); ii. Flocculation in two units (rapid mixing - G > 120 s −1, and slow mixing - G = 20–80 s −1 ), with 0.2–0.5 mg L −1 of flocculant (a cationic polyacrylamide); iii. DAF at a saturation pressure of 6 bar and a 20% water recycling rate. The removal of ions between pH 6.5 and 7.5 was very high, reaching separation efficiencies up to 95% for Pb 2+ and Cu 2+ ions (potential activators of ZnS); the adsorption mechanisms of the uptake of the ions were discussed. The suspended solids (fine particles, <44 µm) were separated by DAF (89–96%) to concentrations <0.5 g L −1 . For higher solid contents, the formed flocs became larger, difficult-to-float and operating conditions required less flocculant and a higher recycling ratio. These high separation efficiencies allowed reuse of water in the lead/zinc sulphide ore rougher flotation stage, avoiding the activation of ZnS flotation. The pilot DAF unit (1.8–2.4 m 3 h −1 flow rate) followed an innovative design by enhancing the height/area rate (6.9 m −1 ), compared to conventional cells; it included specially designed and oriented lamellae and a perforated plate to control internal turbulence. These modifications allowed the enhancement of the hydraulic loading capacity up to 15 m 3  m −2  h −1 (or 15 m h −1 ), more than double the known value for conventional DAF cells (about 7 m h −1 ). Estimations of general costs for a 300 m 3 h −1 treatment plant were calculated and the operating costs reached US$ 0.56 m −3 of treated water. It is believed that this DAF process has a high potential for removing deleterious ions from water at a high removal rate, recycling process water feeding ore flotation plants and minimizing effluent discharge (sometimes polluted).